2010
DOI: 10.1158/1535-7163.mct-09-0638
|View full text |Cite
|
Sign up to set email alerts
|

Proanthocyanidins Inhibit In vitro and In vivo Growth of Human Non–Small Cell Lung Cancer Cells by Inhibiting the Prostaglandin E2 and Prostaglandin E2 Receptors

Abstract: Overexpression of cyclooxygenase-2 (COX-2) and prostaglandins (PG) is linked to a wide variety of human cancers. Here, we assessed whether the chemotherapeutic effect of grape seed proanthocyanidins (GSP) on non-small cell lung cancer (NSCLC) cells is mediated through the inhibition of COX-2 and PGE 2 /PGE 2 receptor expression. The effects of GSPs on human NSCLC cell lines in terms of proliferation, apoptosis, and expression of COX-2, PGE 2 , and PGE 2 receptors were determined using Western blotting, fluores… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
43
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(48 citation statements)
references
References 34 publications
(48 reference statements)
4
43
0
Order By: Relevance
“…Cell viability was determined using an MTT assay. 29 As shown in Figure 2C, treatment of NSCLC cells with honokiol for 48 h resulted in a significant reduction in cell viability in a dose-dependent manner (60 μM dose; 40-70%, p < 0.001). We did not find significant inhibition of cell proliferation of BEAS-2B cells (4-10% inhibition) after honokiol treatment at the concentrations of 10, 20, 40 and 60 μM for 48 h. Moreover, the inhibition of cell viability of BEAS-2B cells by honokiol was significantly lower (p < 0.001) than the effect of equivalent concentrations of honokiol on the NSCLC cells at the same time points.…”
Section: Honokiol Inhibits Cell Growth or Viability Of Human Nsclc Cementioning
confidence: 76%
See 1 more Smart Citation
“…Cell viability was determined using an MTT assay. 29 As shown in Figure 2C, treatment of NSCLC cells with honokiol for 48 h resulted in a significant reduction in cell viability in a dose-dependent manner (60 μM dose; 40-70%, p < 0.001). We did not find significant inhibition of cell proliferation of BEAS-2B cells (4-10% inhibition) after honokiol treatment at the concentrations of 10, 20, 40 and 60 μM for 48 h. Moreover, the inhibition of cell viability of BEAS-2B cells by honokiol was significantly lower (p < 0.001) than the effect of equivalent concentrations of honokiol on the NSCLC cells at the same time points.…”
Section: Honokiol Inhibits Cell Growth or Viability Of Human Nsclc Cementioning
confidence: 76%
“…Cells were treated with honokiol or valproic acid for desired period of time and cell lysates were prepared as detailed previously. 29,43 Proteins were resolved on 8-12% SDS-PAGE and transferred onto the nitrocellulose membrane. Western blot analysis was performed to detect the expression levels of proteins of interest as detailed previously.…”
Section: Disclosure Of Potential Conflicts Of Interestmentioning
confidence: 99%
“…Small randomized trials have found beneficial effects of GSE for diabetic retinopathy and for vascular fragility (2). Recently, preclinical studies have shown that GSE inhibited human non-small cell lung cancer (NSCLC) xenografts growth in mice, in part, through the inhibition and downregulation of cyclooxygenase-2 (COX-2) and prostaglandin (PG) E 2 eicosanoid pathways (3).…”
Section: Introductionmentioning
confidence: 99%
“…For this study, we used the peripheral airway-derived adenocarcinoma cell line A549, because adenocarcinoma is currently the most common form of lung cancer and COX-2 levels are significantly higher in adenocarcinomas than in squamous cell carcinomas (26). For a positive control we used the non-selective COX inhibitor indomethacin, which has been proven to inhibit COX-2 activity and expression in NSCLC cells (27,28).…”
Section: Introductionmentioning
confidence: 99%